The Impact of the Prehistoric Out-of-Africa Migration on Cultural Diversity - Oded Galor; Marc Klemp; Daniel C. Wainstock (Center for Economic Studies and ifo Institute (CESifo), 2023)
Evidence suggests that the prehistoric Out of Africa Migration has impacted the degree of intra-population genetic and phenotypic diversity across the globe. This paper provides the first evidence that this migration has shaped cultural diversity. Leveraging a folklore catalogue of 958 oral traditions across the world, we find that ethnic groups further away from East Africa along the migratory routes have lower folkloric diversity. This pattern is consistent with the compression of genetic, phenotypic, and phonemic traits along the Out of Africa migration routes, setting conditions for the emergence and proliferation of differential cultural diversity and economic development across the world.
Keywords: O10; Z10; 330; diversity; culture; Out of Africa; folklore